Blockchain-Powered Digital Identity Management for Secure Digital Payments - Vijay Kumar Soni (International Journal of Intelligent Systems and Applications in Engineering, 2024)
As digital payment ecosystems continue to expand, the need for secure, efficient, and privacy-preserving identity verification becomes increasingly vital. Traditional identity management systems, based on centralized or federated models, often suffer from vulnerabilities such as data breaches, limited user control, poor interoperability, and regulatory compliance challenges. This paper proposes a blockchain-based digital identity framework that addresses these limitations by leveraging Decentralized Identifiers (DIDs), Verifiable Credentials (VCs), and Self-Sovereign Identity (SSI) principles. In this framework, users securely store their credentials such as mobile driving licenses (mDLs) according to ISO 18013-5 in identity wallets, allowing selective disclosure of personal characteristics while retaining complete control over their information. The solution addresses these needs by improving trust, security, user control, and cross-platform interoperability, while complying with major international data protection laws like GDPR, CCPA, and Dodd-Frank Act CFPB Rule 1033. These laws highlight the consumer’s right to consent data sharing and increased transparency. Additionally, the study investigates the activities of global standardization organizations such as EMVCo, the OpenID Foundation (OID4VC and OID4VCI protocols), and the Decentralized Identity Foundation (DIF) in promoting large-scale adoption, interoperability, and security of decentralized identity systems. Comparative analysis proves that blockchain-based identity frameworks are superior to conventional centralized and federated systems on several parameters such as security, trust, usability, interoperability, and cost-effectiveness. The results show the revolutionary capability of decentralized identity in digital payment systems, enabling a more secure, user-controlled, and transparent digital economy. This research unveils new research avenues for the future growth of scalable and compliant decentralized identity solutions.